2022
DOI: 10.14687/jhs.v19i2.6248
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of basic psychological needs of leisure time of Faculty of Sport Sciences students in terms of some variables

Abstract: Objective: In this study, the basic psychological needs of sports sciences students at leisure time were analyzed in terms of certain variables. The population of the study is the students from the faculty of sports sciences. Method: The questionnaire which was used to collect the related data in the study consists of two parts. The personal information form created by the researcher, and in the second section, Basic Psychological Needs Scale in Leisure Activity (BPNSLA), which was adapted into Turkish by Güne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…According to the Independent Sample T-test result between gender variables and Basic Psychological Needs in Leisure Activity and Life Satisfaction, a statistically significant difference was detected in favour of male participants only in the variable of relatedness sub-dimension (p<0.05). Özmaden et al (17), in their study with sports sciences students, concluded that as a result of the analysis between the leisure psychological needs of the participants and the gender variable, a situation occurred in favour of female participants in the autonomy sub-dimension. Yasul (31) concluded in a thesis study that there was no statistically significant difference in terms of gender variable in the Autonomy, Relatedness, and Competence sub-dimensions of the basic psychological needs scale.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Independent Sample T-test result between gender variables and Basic Psychological Needs in Leisure Activity and Life Satisfaction, a statistically significant difference was detected in favour of male participants only in the variable of relatedness sub-dimension (p<0.05). Özmaden et al (17), in their study with sports sciences students, concluded that as a result of the analysis between the leisure psychological needs of the participants and the gender variable, a situation occurred in favour of female participants in the autonomy sub-dimension. Yasul (31) concluded in a thesis study that there was no statistically significant difference in terms of gender variable in the Autonomy, Relatedness, and Competence sub-dimensions of the basic psychological needs scale.…”
Section: Discussionmentioning
confidence: 99%